Snow cover is a neglected driver of Arctic biodiversity loss. Issue 11 (November 2018) - Niittynen, Pekka; Heikkinen, Risto; Luoto, Miska
Abstract Snow has far-reaching effects on ecosystem processes and biodiversity in high-latitude ecosystems, but these have been poorly considered in climate change impact models1, 2 . Here, to forecast future trends in species occurrences and richness, we fitted species–environment models with temperature data from three climate scenarios and simulated up to a 40% decrease in snow cover duration (SCD)3 . We used plot-scale data on 273 vascular plant, moss and lichen species in 1, 200 study sites spanning a wide range of environmental conditions typical for mountainous Arctic landscapes (within 165 km2 ). According to the models, a rise in temperature increased overall species richness and caused only one species to lose all suitable habitat. In contrast, a shorter SCD tempered the effect of increasing temperature on species richness and led to accelerated rates of species' local extinctions after a tipping point at 20–30% SCD decrease. All three species groups showed similar extinction rates but contrasting species richness responses. Our simulations indicate that future biodiversity patterns in Arctic regions are highly dependent on the evolution of snow conditions. Climate impact models that ignore the effects of snow cover change may provide biased biodiversity projections, with potentially erratic implications for Arctic nature conservation planning. Arctic biodiversity patterns will be highly dependent on the evolution of snow conditions, according to simulation results that integrate observations of vascular plants, mosses and lichens over a range of Arctic landscapes.